THE DEVELOPMENT OF SOCIAL MEDIA, PARTICULARLY THE GOOGLE SITE - Ahmedov Azimjon Ilhomovich the teacher of Andijan State Institute of Foreign Languages Qaxarova Go’zal (ZAMONAVIY TA’LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2023)
Abstract: This article covers the history and development of Google’s social network, the most important messages in it.